3,6 x 56 - 3,6 x 12 - 3,6 x 3,4
= 3,6 x ( 56 - 12 - 3,4 )
= 3,6 x 40,6
= 146,16
hoc tot
3,6 x 56 - 3,6 x 12 - 3,6 x 3,4
= 3,6 x (56 - 12 - 3,4)
= 3,6 x 40,6
= 146,16
HT
3,6 x 56 - 3,6 x12 - 3,6 x 3,4
= 3,6 x ( 56 - 12 -3,4 )
= 3,6 x 40,6
= 146,16
\(3,6\times56-3,6\times12-3,6\times3,4\)
\(=3,6\times\left(56-12-3,4\right)\)
\(=3,6\times40,6\)
\(=146,16\)
3,6 * 56 - 3,6 * 12 - 3,6 * 3,4
= 3,6 * ( 56 - 12 - 3,4 )
= 3,6 * 40,6
= 146,16
3,6 x 56 - 3,6 x12 - 3,6 x 3,4
= 3,6 x ( 56 - 12 - 3,4)
= 3,6 x 40,6
= 146,16
`Hok T~
3,6 x56 - 3,6 x12 -3,6 x3,4
=3,6 x (56-12-3,4)
=3,6 x40,6
=146,16